PEMBERIAN ASIMILASI DAN INTEGRASI TERHADAP NARAPIDANA GUNA PENCEGAHAN DAN PENANGGULANGAN COVID 19 - Putra Aditya Bagus S; Mitro Subroto (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This writing is based on the policies that have been set regarding the assimilation program for prisoners during the COVID-19 pandemic. Assimilation is an important thing for inmates to get a change in attitude/behavior about what it is to actually serve a prison sentence, because in prison there are many different cultures and characters. In the process of assimilation, it can not be considered easy to see from environmental conditions and changes in society. Assimilation is given to prisoners in order to fulfill the conditions that apply in accordance with the rule of law and this is a form of fulfilling the rights of prisoners. Assimilation is a program established by the government for guidance for adult and child prisoners and they are returned to the community environment and live their lives as usual with the community. Integration is a conditional release covering (PB, CB, CMB) for prisoners who have met the requirements in accordance with existing provisions. The government issued Regulation of the Minister of Law and Human Rights Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration Rights for Prisoners and Children in order to prevent and cope with the spread of Covid-19 in prisons or detention centers, assimilation programs are provided and will be carried out at home under guidance and supervision.